A Decade after the 2009 Global Recession : Macroeconomic Developments - Koh, Wee Chian; Yu, Shu (World Bank, Washington, DC, 2020)
Emerging markets and developing economies (EMDEs) weathered the 2009 global recession relatively well. However, the impact of the global recession varied across economies. EMDEs with stronger pre-crisis fundamentals -- such as large foreign exchange reserves, sound fiscal positions, and low inflation -- suffered milder growth slowdowns, in part due to their greater capacity to engage in monetary and fiscal stimulus. Low-income countries were also resilient, as foreign aid and inflows of remittances remained relatively stable. In contrast, EMDEs that were heavily dependent on short-term capital flows -- such as portfolio investment and cross -- border bank lending—fared less well, especially those in Europe and Central Asia. A key lesson for EMDEs is the need to strengthen macroeconomic frameworks and create policy space to prepare for future global downturns.